Investing in health the social and economic benefits of health care innovation - Farquhar, Irina; Summers, Kent; Sorkin, Alan (Emerald, 2001)
Public health has, for many years, been concerned with efforts to increase the efficiency of health care delivery, to measure changes in health care resource utilization and associated costs, and to link these changes to different types of interventions. These efforts, as well as collaboration between biopharmaceutical organizations, producers of medical devices, and managed care and public health organizations, have been enhanced by the opportunities created within the fast growing field of outcomes research. This volume presents studies contributing to the enhancement of the outcomes research paradigm by incorporating economic and social interactions within the health care delivery, clinical decision-making and outcomes systems.-A multidisciplinary team of scientists in the fields of outcomes research, pharmacoeconomics, public health, health services research, and health economics address such complex problems as: benefits and cost of advancements in genetic technologies; methodologies for constructing health care utilization and cost estimates; and the effect of insurance type on resource utilization and health outcomes. Other studies consider both the types of drugs purchased and the prices paid, pharmaceutical spending and health outcomes, incremental advantages of newer treatments, willingness to pay measurements, disease-specific impacts on human capital and quality of life, and modelling clinical trial results. One of the most important findings in this book is the description of the role of low energy in the symptomatology of depression and its strong relationship with absenteeism, work productivity and social functioning.-Another paper documents the disease-specific mortality, case-fatality and annual health care utilization in diabetics and establishes the association of respiratory conditions with elevated mortality among diabetics. The work contains other papers which provide significant results in cardiovascular, infectious, central nervous system disease areas as well as in quality of life and health outcomes measurements.
Keywords: Medical care -- Coste effectiveness.; elektronické knihy; electronic books